Structural Equation Model of Factors Affecting the Digital Transformation of Industrial Business in Rayong Province - Subanjui, Rungroj; Pansantia, Chainat (Journal of Information Science Research and Practice, 2021)
Purpose: This investigation focuses on the development of structural equation model of factors affecting the digital transformation of industrial business in Rayong province. Methodology: The indicators were derived from a review of related literature and research papers. The data were collected from a sample of 304 top executive operators or their representatives of the industrial business in the province. The research instrument for measurement was a five-point scale questionnaire, and the data were analyzed using structural equation modeling. Main Findings: The study findings indicated that the structural equation model of factors impacting the success of industrial business in Rayong province corresponded to the literature and empirical studies at p-value = 0.06, CFI = 0.97, ႿGFI = 0.95, AGFI = 0.93, RMR = 0.04, SRMR = 0.04, RMSEA = 0.03, and p =.01 which met the criteria set for the results of variable analysis in the newly developed model. When considering overall effect of the model, it was found that transformation in leadership, organization and staff had a significantly direct effect of the success of digitization with the highest impact being the organization (TE = 0.l33), followed by the staff (TE = 0.21), and the leadership (TE = 0.14). Moreover, the leadership had indirect effect on the digitization success through the organization (IE = 0.18) and the staff (IE = 0.10) Applications of the study: This study provides awareness of factors impacting digital transformation of the industrial business sector in Rayong province. This transformation is not only a part of its objective achievement but also a business advantage over competitors in order to stay alive in business. In addition, the findings of this investigation can be used in industrial business elsewhere.